A piezoelectric vibration energy harvester for multi-directional and ultra-low frequency waves with magnetic coupling driven by rotating balls. (15th March 2022) - Shi, Ge; Tong, Dike; Xia, Yinshui; Jia, Shengyao; Chang, Jian; Li, Qing; Wang, Xiudeng; Xia, Huakang; Ye, Yidie
Graphical abstract: Highlights: The harvester can harvest vibration energy from any direction. The harvester can harvest energy from ultra-low frequency waves. The harvester can up-convert the excitation frequency through impulse-like magnetic force. The harvester is designed with a new rolling ball driving structure. A significant generated power of 6.32mW (at 0.9 Hz) is obtained. Abstract: Wave vibration is a ubiquitous energy existing in our environment, but efficient vibration energy harvesting at ultra-low frequency and multi-directions is still a challenge. This paper proposes a piezoelectric vibration energy harvester for multi-directional and ultra-low frequency waves driven by a rotating rolling ball. The energy harvester is designed to float on the water's surface; it will be tilting vibration in the corresponding direction once driven by the wave from any direction. The energy harvester converts the vibration wave energy into electrical energy due to the basic characteristics of frequency up-conversion. The proposed harvester can efficiently scavenge not only ultra-low frequency but also multi-directional vibration wave energy. The energy harvester is modeled and designed. A simulation wave device is used to evaluate the proposed harvester's performances. Simulation and experimental results are in good agreement. The energy harvester can harvest energy from single-direction or multi-direction excitation. When the external frequency is 0.9 Hz, and the external load is 47KΩ, the power output of the whole energy harvester is 6.32mW, which shows great application prospects in the power supply of ocean buoys.